Can financial literacy drive microentrepreneur success in digital economies? - Muhammad Ramadhani Kesuma; Lusiana Desy Ariswati; Margareth Henrika; Chandika Mahendra Widaryo; Ellen D. Oktanti Irianto; Rohana Nur Aini (Journal of Economics Research and Policy Studies, 2025)
Microentrepreneurship significantly contributes to economic development in resource-rich regions like East Kalimantan, yet faces challenges due to low financial literacy and limited digital adoption. Existing research highlights the importance of financial literacy for business success, but underexplores the role of digital financial literacy and regional contexts. This study investigates how financial literacy and digital financial literacy influence microentrepreneur success, with financial planning as a mediating factor. Using a quantitative approach with Partial Least Squares Structural Equation Modeling, data were collected from 160 microentrepreneurs in East Kalimantan. The findings reveal that financial literacy directly enhances business success, while digital financial literacy impacts success indirectly through financial planning. The model explains 60.8% of the variance in microentrepreneur success, emphasizing the critical role of structured financial strategies. These results suggest that integrating digital tools into financial education can foster sustainable business growth.